Pelatihan Pembuatan Sabun Cuci Piring sebagai Stimulus Kewirausahaan di Desa Gunung Tinggi: Analisis SWOT untuk Perumusan Rekomendasi Keberlanjutan Usaha - Dio Sanda; Bayu Andika; Masleni Nasution; Afsah Sandy Tarigan (Pusat Riset dan Inovasi Nasional, 2026)
Economic development in rural areas, specifically, aims to improve community welfare. However, in practice, many challenges remain, such as limited technical skills, minimal innovation, and low community capacity to create and develop productive businesses. One way to address these challenges is through human resource empowerment. Gunung Tinggi Village has the potential to develop creative businesses, particularly among housewives, such as dishwashing soap. This product is a household necessity that is used routinely, so demand tends to be sustainable. Therefore, a SWOT analysis was used to provide sustainability recommendations for this business. The methods used included service learning (SL) with a Participatory Action Research (PAR) approach to ensure active participant involvement and the program's alignment with the community's real needs. The results showed that the initial impact of this Community Service Program (PKM) activity was evident in the production of marketable products and the opening of new business opportunities, which directly contributed to the diversification of income sources and increased family economic independence. Furthermore, the application of SWOT analysis proved effective as a tool in formulating sustainability strategies for the micro-enterprises being developed.